Satellite-based digital platform for rice production and climate impact monitoring in Mali - Mathieu, Renaud; Dossou-Yovo, Elliott; Holecz, Francisco; Murusegan, Deiveegan; Quicho, Emma; Akpoffo, Marius; Gatti, Luca (Accelerating Impacts of CGIAR Climate Research for Africa, 2025)
Rice is a staple crop in Mali and plays a vital role in the country's economy, food security, and social structure. Rice is primarily grown in both irrigated and rainfed ecosystems, in the major rice-growing regions including Ségou, Mopti, Timbuktu, Sikasso and Selingue. Despite the growing demand for rice due to population expansion, rice farming in Mali faces challenges, including climate variability. Effective monitoring of rice production through remote sensing technologies is essential for optimizing crop yields, managing resources efficiently, mitigating the impacts of climate change, and addressing climate risks. The Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project, in collaboration with national and regional partners, supports climate resilience through climate risk mapping, crop monitoring, and climate impact assessments. Since 2022, IRRI, AfricaRice, and sarmap, has been piloting a digital monitoring rice production platform in Mali, with a focus in the Segou/Mopti region (Office du Niger) and Sikasso Circle, as part of Phase I. Phase II (2024-2025) aims to upscale and validate the platform at national scale, further improve performance and adaptation to regional production systems, as well as facilitate its uptake into the national digital information system, through adequate advocating and institutionalization interventions, and advanced training. This report outlines the objectives, methods and activities undertaken in the first half of 2025 of the remote sensing-based rice monitoring initiative in Mali, as part of the Accelerating Impacts of CGIAR Climate Research in Africa project.